Effect of Ginger Warm Compresses on Pain Intensity Reduction in Patients with Rheumatoid Arthritis - Hamdana; Edison Siringoringo; Eka Rahayu Nensi (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2018)
Rheumatoid arthritis is a musculoskeletal disease that affects many people, this disease causes many complaints including, pain in the legs, knees and various other joints. One of the non-pharmacological measures that can be done to reduce the intensity of pain is warm ginger compresses. Ginger contains essential oils with active ingredients school, gingerol, paradol and zingerone which are warm and can promote blood circulation. This study aims to determine the effect of ginger warm compresses on the reduction in pain intensity in patients with rheumatoid arthritis. This type of research is a pre-experiment with one group design pre-post test design. This research was conducted in May-2017. The samples in this study were 15 people who suffered from rheumatoid arthritis pain with consecutive sampling data collection techniques. The results showed the intensity of rheumatoid arthritis pain before the warm ginger compress (pre-test) was average with moderate pain intensity. While the intensity of pain after a warm ginger compress (post-test) is average with mild pain intensity. Based on Wilcoxon's alternative paired t-test, p-value 0,000 (<0.05) means that there is a significant influence between the effect of warm ginger compresses on the decrease in pain intensity in patients with rheumatoid arthritis. It is hoped to further develop several variables and add a long time to the administration of warm ginger compresses in rheumatoid arthritis so that the results of research on ginger warm compresses to reduce pain intensity in patients with rheumatoid arthritis are more optimal and can provide more accurate research results.